Evaluation of immediate effect of foot massage on patient's vital signs in a general intensive care unit - Shaban; M. Haj Amiry; P. Mehran; A. Kahrary; S (Tehran University of Medical Sciences, 2004)
Introduction: Massage of the limbs is a safe procedure that could have therapeutic effects and cause physical and psychological relaxation of patients in intensive care unit (ICU). Materials and Methods: This survey is a quaziexperimental study that assessas immediate effects of foot massage on patient's vital signs in a general ICU. After a pilot study, a sample size of 50 patients was chosen. A questionnaire about demographic data and a 3-table checklist for recording vital signs (heart rate, peripheral O2 saturation and mean arterial pressure) was used. The data gathered by interview and physiologic measurement. For every patient, vital signs were recorded every 1 minute interval for 5 minutes (after completing the demographic data). Then foot massage was applied for five minutes and during the massage patients' vital signs recorded every minute. Immediately the patients' vital sings were recorded every minute for five minutes. The mean of each parameter was calculated and compared the values at baseline, during massage, and after massage. Results: The findings showed that there was a significant difference between mean heart rate, mean arterial pressure and mean spO2 before and during foot massage (p<0.0001). Difference between mean heart rate, mean spO2 and mean arterial pressure during and after foot massage was not significant but, deference of mean heart rate and mean arterial pressure before and after massage was significant (p< 0.0001). Difference of mean spO2 before and after massage was also significant (p<0.003). Conclusion: According to the findings of this study, foot massage has a potential beneficial effect on patients vital signs and last at least for 5 minutes. This effect could be due to increasing relaxation which moderates the changes of vital signs, caused by stress.